Wole Soyinka : literature, activism, and African transformation - Dauda, Bola; Falola, Toyin (Black literary and cultural expressions, 2022)
"This timely and expansive biography of Wole Soyinka, the Nigerian writer, Nobel laureate, and social activist, shows how the author's early years influence his life's work and how his writing, in turn, informs his political engagement. Three sections spanning his life, major texts, and place in history, connect Soyinka's legacy with global issues beyond the borders of his own country, and indeed beyond the African continent. Covering his encounters with the widespread rise of kleptocratic rule and international corporate corruption, his reflection on the human condition of the North-South divide, and the consequences of postcolonialism, this comprehensive biography locates Wole Soyinka as a global figure whose life and works have made him a subject of conversation in the public sphere, as well as one of Africa's most successful and popular authors. Looking at the different forms of Soyinka's work--plays, novels, and memoirs, among others--this volume argues that Soyinka used writing to inform, mobilize, and sometimes incite civil action, in a decades-long attempt at literary social engineering"--